CONCEPÇÕES DE ENSINO DE HISTÓRIA PRESENTES NOS INSTRUMENTOS AVALIATIVOS DE UMA ESCOLA MUNICIPAL DE IRATI-PARANÁ - CHEPLUKI, FRANCIELLI CZELUSNIAK COSTA (2023)
This research address the themes of historical learning, teaching of history and educational evaluation, where an analysis of the evaluation instruments of History is presented in a municipal school in Irati – Paraná, in its initial years (3rd to 5th year). To answer the question of this research: “wich conceptions of history teaching are present in the evaluation instruments?” we carried out a documentary analysis and possession of the selected sources; the evaluative instruments of history, we created categories of analysis from the teories of teaching History and History education to understand which of these categories they best fit. Inserting a qualitative method, the bibliographical research through references of texts, books, articles by specialist theorists in the area of Learnig Assessment, Educational Assessment, History Teaching and Historical Education, we consulted the following authors: Jörn Rüsen (2001, 2010, 2012, 2014), Barca (2001, 2012, 2018), Lee (2001, 2008), Schmidt (2017), Bittencourt (2018), Arredondo e Diago (2013), Freitas (2014), Luckesi (2011, 2018). The field of research used was that of Historical Education, a field that is part of the Teaching of History, and which aims in its research to understand the student´s historical learning from a scientific nature of the epistemology of History Based on this work, the intention is that primary school teachers in the initial series come to enjoy and benefit from, as generalist conductors not trained in History, and their evaluative practices come to be reflected from the student´s learning. At the end of the documental analysis of the evaluative instruments, we concluded that the category of teaching history as Social Studies was the most present in the instruments analyzed, which is justified by the curriculum of the History discipline in Paraná in the initial grades, which in this content contemplates the organization of from around to farthest. We also noticed presuppositions of historical learning in several of the sources analyzed, but in an isolated way, the students´historical learning did not materialize based on these evaluations.